Nanomedicine-Driven Approaches for Kartogenin Delivery: Advancing Chondrogenic Differentiation and Cartilage Regeneration in Tissue Engineering - Bhuyan S; Swain S; Misra RDK; Rautray TR (International Journal of Nanomedicine, 2025)
Samapika Bhuyan,1,* Subhasmita Swain,1,* RDK Misra,2 Tapash R Rautray1 1Biomaterials and Tissue Regeneration Laboratory, Centre of Excellence, Siksha ‘O’ Anusandhan (Deemed to be University), Bhubaneswar, Odisha, India; 2Metallurgical, Materials and Biomedical Engineering Department, The University of Texas at El Paso, El Paso, Texas, 79968, USA*These authors contributed equally to this workCorrespondence: Tapash R Rautray, Email tapashrautray@soa.ac.in RDK Misra, Email dmisra2@utep.eduAbstract: Articular cartilage degradation and osteocartilage defects are the most prevalent concerns that vary from localized to more systemic forms of cartilage disease. However, regulating chondrogenic differentiation within the joints remains a significant challenge. Kartogenin, a small heterocyclic compound, has recently garnered considerable attention as a potential therapeutic agent, owing to both chondrogenic and chondroprotective properties for intra-articular therapy. Initially, it was created for osteoarthritis; it has also been used to address various diseased conditions, such as the regeneration of disc and bone-tendon junctions. On top of that, it preserves the equilibrium between cartilage catabolism and anabolism, while also mitigating inflammation and alleviating pain by preventing damage induced by cytokines. To modulate tissue function and cellular behaviour, it is crucial to have sustained release of ketogenic through an appropriate delivery system. A multitude of biomaterial-based carriers have been developed for the prolonged release of kartogenin. Moreover, many biological mechanisms of action of kartogenin have been identified. The most critical molecular mechanism among them is the dissociation of filamin A from core-binding factor (CBF)-β induced by kartogenin. Filamin A subsequently translocates to the nucleus, where it engages with RUNX-1 to transcribe genes implicated in the chondrogenesis of mesenchymal stem cells. This review focuses on the development of biomaterials functionalized with kartogenin, including their structure, design, physicochemical properties, biological roles, molecular mechanisms of action, and applications in tissue engineering and regenerative medicine. In conclusion, we discussed the future possibilities and challenges posed by recent advancements in kartogenin research and their potential applications in tissue regeneration.Keywords: Kartogenin, cartilage regeneration, osteoarthritis, TGF-β, chondrogenesis